Enhanced thermoelectric properties of Cu1.8S by Ti-doping induced secondary phase - Liang, Dou-Dou; Zhang, Bo-Ping; Zou, Liang (Journal of alloys and compounds, 2018)
Cu1.8S is a promising thermoelectric material with characteristics of superionic conductors. This study has been focused on the effect of Ti4+ doping on both electron and phonon transport properties of TixCu1.8-xS (x = 0, 0.04, 0.07, 0.10). The thermoelectric figure of merit (ZT) was greatly enhanced when 0.07 ≤ x ≤ 0.10, mainly due to a decreased thermal conductivity (0.62–0.77 Wm−1K−1) caused by the formation of the lower-conductive Cu4(TiS4) and Cu1.96S second phases, and the introduced point defects. Along with an improved Seebeck coefficient, a peak ZT value of 0.54 at 673 K was obtained in the Ti0.07Cu1.73S composition, which is twice as large as that of the undoped one. A maximum efficiency of about 3.7% at Th = 673 K with a proper output power density (Pd∼0.56 Wcm−2) was obtained. Our results indicate that the introduction of Ti4+ in copper sulfide thermoelectric materials is an effective and convenient strategy to improve ZT by decreasing thermal conductivity. •An improved α and low κ (0.62–0.77 Wm−1K−1) produced by the second phases by adding Ti4+ in Cu1.8S.•The highest ZT up to 0.54 at 673 K is twice as large as that of the undoped one.•A maximum efficiency of 3.7% at Th = 673 K with a proper Pd∼0.56 Wcm−2 was obtained.